PEMANFAATAN AMPAS KOPI SEBAGAI ARANG AKTIF UNTUK ADSORBEN RHODAMIN B - Evifania Juvita Anggriani (JURNAL KIMIA MULAWARMAN, 2020)
Research on the use of coffee grounds activated carbon as an adsorbent to reduce the content of Rhodamine B dye has been carried out. The activated carbon used is chemically activated by immersion using 1 M H3PO4 solution for 24 hours then burned at 500ËšC for 45 minutes, while physically activated it is carried out by burning at 500ËšC for 45 minutes. The results of the study which showed the characteristics published in SNI 06-3730-1995, the optimum conditions of Rhodamine B adsorption on both activated carbon at pH 7 and contact time at 15 minutes. Rhodamine B adsorption isotherms on chemically and physically activated carbon using Langmuir adsorption isotherm models with adsorption capacities are 1.6943 mg/g and 1.5936 mg/g, respectively. Chemical and physics activated coffee grounds activated carbon were applied to reduce Rhodamine B from sarung waste in Samarinda. Decrease of Rhodamine B levels in 25 mL of waste samples containing Rhodamine B 14.1860 mg/g with 1 gram of adsorbent were 89.1125% and 60.7923%, respectively. Keywords: Activated carbon, Spent coffee grounds, Rhodamine B, Adsorption